Bit-to-Symbol Mapping Based on Erroneous Bits Minimization for High-Dimensional Modulation Format - Guijun Hu; Dan Hou; Li Yan; Enock Kashero (IEEE Photonics Journal, 2016)
In this paper, we propose a novel high-dimensional mapping scheme based on erroneous bits minimization. Analysis and simulation results show that the proposed mapping can improve the bit-error-rate (BER) performance in comparison with random mapping and Millar mapping. It is also shown that the computational complexity of erroneous bits minimization mapping is much lower than that of Millar mapping.